South African youth ministry: A hermeneutical agency in the lives of young people - Aziz, Garth (Stellenbosch Theological Journal, 2026)
Youth ministry, as a practical theological discipline, has surpassed the traditional concept of being a department of the church and is no longer satisfied with being fragmented to serve as a program-based babysitting club, department for evangelistic outreach to young people, discipleship class for new believers, or a leadership incubator within the church. Youth ministry, as a legitimate ministry of the church, serves as a hermeneutical agent in the lives of young people. As a hermeneutical agency, youth ministry has the transformation of the individual as its core function by facilitating young people to have and experience a deep and meaningful relationship with God. The implications, therefore, are that youth ministry must reflect on and interpret the lived contexts of young people to reconcile how God is experienced within their lives and lived contexts. This article, therefore, will investigate how youth ministry can serve as a hermeneutical agency in the lives of young people, so that they may recognise and interpret God’s actions in their lives. This study employs a conceptual methodology, using critical literature analysis, theological reflection on Scripture, tradition, and context, and Osmer’s four tasks of practical theology as its guiding method. Based on a practical theology framework, the findings indicate that youth ministry can harmonise orthodoxy and orthopraxy by interpreting the lived experiences of young people, addressing systemic challenges, and cultivating theology that is grounded in African contexts.